STICKLEBACK COLOR FLUCTUATION OVER THE BREEDING SEASON: AN IN DEPTH FIELD STUDY - Bowling, Tyler B. T. (East Carolina University, 2018)
The coloration of the threespine stickleback (Gasterosteus aculeatus) is well studied in the field of evolution, mainly with regard to the role of sexual selection (Ostlund-Nilsson et al., 2006; Foster et al., 2008; Hendry et al., 2013). Recent studies, however, suggest that natural selection has a larger impact on stickleback coloration than previously thought (Candolin and Tukiainen, 2015). In the present study we tested three competing hypotheses: 1) color patches function mainly in courtship; 2) color patches function mainly in egg and fry defense; or 3) patches function in courtship and late egg/fry defense. We tested these hypotheses by comparing variation in color intensity of males across nesting phases and in relation to stage or presence of offspring, and their development. We predicted that if red intensity peaked during courtship, hypothesis 1 would be supported. Alternatively, increasing red intensity during the parental phase would support hypothesis 2, with natural selection being the main force at work on the color patterns, conflicting with dogma. Our data showed that throat and, to a lesser degree, jaw color patterns were consistent with a major role for sexual selection. Alternatively, spine coloration could be the result of multiple selective pressures.
Keywords: Threespine stickleback--Genetics; Evolutionary developmental biology; Fishes--Color